Factors Associated With Mothers' Level Of Knowledge About Child Growth And Development At Tk Negeri Pembina, Tilango Sub-District Gorontalo District - Sudirman, Andi Akifa; Rokani, Muryati; Siu, Megi Puspita (Sean Institute, 2024)
Growth and development in children is a continuous process that begins at conception and continues until adulthood. Disorders in growth and development can impact a child's future development and may lead to disability. Several factors affect child growth and development, including age, education, and maternal employment. This study aims to determine the relationship between maternal age, education, and occupation with the level of maternal knowledge about child growth and development. The study used a quantitative research design with an analytic survey and cross-sectional approach. The population consisted of 46 mothers, with a sample size of 46 using total sampling. The results showed that the majority of mothers were aged 20-35 years (32 mothers, pValue = 0.016), had secondary education (22 mothers, pValue = 0.029), and were not employed (31 mothers, pValue = 0.011). Most mothers had good knowledge about child growth and development (36 mothers). There is a significant relationship between maternal age, education, and employment with the level of maternal knowledge about child growth and development. It is recommended that mothers regularly monitor their children's growth and development at the posyandu and seek information about child growth and development from health workers.